(untitled) (INTERNATIONAL CONFERENCE ON ANALYSIS OF MATHEMATICS AND EXACT SCIENCES, 2024)
Aleksandr Feinberg is well-known poet of Uzbekistan, who dedicated his whole life and career to promote Uzbek culture and custums. Looking through his poems, it could be seen Feinberg’s kindness and gratitude for Uzbek people